2010
DOI: 10.1371/journal.pone.0015379
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of the N- and C-Terminal Regions of the Human Mitochondrial Single-Stranded DNA-Binding Protein

Abstract: Biochemical studies of the mitochondrial DNA (mtDNA) replisome demonstrate that the mtDNA polymerase and the mtDNA helicase are stimulated by the mitochondrial single-stranded DNA-binding protein (mtSSB). Unlike Escherichia coli SSB, bacteriophage T7 gp2.5 and bacteriophage T4 gp32, mtSSBs lack a long, negatively charged C-terminal tail. Furthermore, additional residues at the N-terminus (notwithstanding the mitochondrial presequence) are present in the sequence of species across the animal kingdom. We sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 48 publications
(73 reference statements)
0
47
0
Order By: Relevance
“…5A). It has been shown that mtSSB stimulates unwinding by TWINKLE by almost 8-fold in a helicase assay similar to the M13-based unwinding assay that we have used here (24). Because the heterologous T7 gp2.5 stimulates the helicase activity of TWINKLE, it appears that the stimulation by single strand-binding proteins is not protein-specific.…”
Section: Unwinding Activity Of Twinkle Is Facilitated By Trapping Of mentioning
confidence: 72%
“…5A). It has been shown that mtSSB stimulates unwinding by TWINKLE by almost 8-fold in a helicase assay similar to the M13-based unwinding assay that we have used here (24). Because the heterologous T7 gp2.5 stimulates the helicase activity of TWINKLE, it appears that the stimulation by single strand-binding proteins is not protein-specific.…”
Section: Unwinding Activity Of Twinkle Is Facilitated By Trapping Of mentioning
confidence: 72%
“…A 15-mer oligodeoxynucleotide complementary to M13 DNA was synthesized in an Applied Biosystems oligonucleotide synthesizer and then used to prepare the singly primed M13 DNA for DNA polymerase assays as described previously (18). The 48-mer oligodeoxynucleotide used in gel mobility shift assays was as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…Among these proteins, only SSB has been clearly identified in mitochondria. The mitochondrial SSB has a prokaryotic origin and exists in a homotetramer form in both yeast and human (93)(94)(95)(96). Yeast mitochondria also harbor the well-defined Holliday junction resolvase Mgt1/Cce1 (see above).…”
Section: Genes Affecting Mtdna Recombinationmentioning
confidence: 99%
“…This phenotype is suppressed by overexpressing the mitochondrial single-strand binding protein Rim1 (93). Mitochondrial SSB is known to stimulate DNA helicase activity (96). Indeed, Rim1 stimulates Pif1 activity by 4-to 5-fold, and these two proteins physically interact with each other (103).…”
Section: Figmentioning
confidence: 99%